El consultorio jurídico gratuito UNACH centro de privación de la libertad Chimborazo N°1 en el acceso a beneficios penitenciarios y protección de derechos de los PPL - Vilema Vimos, Omar Cayetano (2024)
This research assesses the role of the Free Legal Clinic of UNACH at the Chimborazo N°1 Penitentiary in providing access to penitentiary benefits and protecting the rights of individuals deprived of liberty (IDL). Despite state protection, this priority group has been left vulnerable in terms of its basic needs, including legal requirements. The study identifies the vulnerable condition of IDL and the challenges they face in accessing justice as a legal issue, and from this, analyzes the Clinic's efforts in addressing the legal needs of this priority group. The management of the Legal Clinic, through its advisory and representation services, constitutes the legal mechanism by which the rights of individuals deprived of liberty are protected and assistance is provided in gathering the necessary requirements for access to a change in the social rehabilitation regime, thereby demonstrating the academic community's strong commitment to vulnerable groups. The methodology employed was based on the dogmatic, analytical, and inductive methods, utilizing a qualitative approach and adapting the research strategy to instruments where the sample, consisting of users of the Clinic and members of its administrative structure, was selected non-probabilistically for convenience. Through these strategies, it was concluded that the Free Legal Clinic of UNACH at the Chimborazo N°1 Penitentiary provides a solution to the issues faced by individuals deprived of liberty (IDL), which are exacerbated by the current Ecuadorian penitentiary crisis. Despite the challenges of providing legal services within a penitentiary, the Clinic has proven effective in managing legal procedures, resulting in a notable positive perception among its users regarding the satisfaction of their needs, a situation that has also been corroborated by members of the Clinic's administrative structure.